2017
DOI: 10.1109/jbhi.2016.2558540
|View full text |Cite
|
Sign up to set email alerts
|

Automated Analysis and Quantification of Human Mobility Using a Depth Sensor

Abstract: Analysis and quantification of human motion to support clinicians in the decision-making process is the desired outcome for many clinical-based approaches. However, generating statistical models that are free from human interpretation and yet representative is a difficult task. In this paper, we propose a framework that automatically recognizes and evaluates human mobility impairments using the Microsoft Kinect One depth sensor. The framework is composed of two parts. First, it recognizes motions, such as sit-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 35 publications
1
30
0
Order By: Relevance
“…In the current study, we demonstrate a much simpler method of calculating CoM, first used by Leightley et al [28], is able to achieve similar results. Leightley's method takes the euclidean mean of 3, well-tracked joints (hip left, hip right, spine mid) to be a good estimate of the CoM position.…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…In the current study, we demonstrate a much simpler method of calculating CoM, first used by Leightley et al [28], is able to achieve similar results. Leightley's method takes the euclidean mean of 3, well-tracked joints (hip left, hip right, spine mid) to be a good estimate of the CoM position.…”
Section: Introductionsupporting
confidence: 72%
“…Frame-wise calculation of CoM The position of CoM was calculated, frame-by-frame by taking the euclidean average of the left-hip, right-hip and mid-spine joints, as defined by Eq 2, first used by Leightley et al [28]. This method estimates the position of CoM in three dimensions without needing to rely on the assumptions made by the Balance Master.…”
Section: Recording Of Com Pathmentioning
confidence: 99%
“…In recent years, wearable sensors have been widely used in gait speed estimation [28] and the assessment of a user's health state, while being based on gait abnormalities [29] and fall detection [30]. Some studies recognize and evaluate the daily activities through Microsoft Kinect sensors which measured concurrently with a 3D Mo-Cap system (gold standard), with the result showing that the Microsoft Kinect sensors can effectively identify the characteristics of patients' daily activities and, hence, that it can be used as an effective clinical evaluation method [31,32]. Wearable devices are also widely used to track human walking activities [33].…”
Section: Introductionmentioning
confidence: 99%
“…After normalisation, a set of features, shown in Table II, was calculated. Although the Kinect camera provides coordinates for 25 joints, we found that features derived from just the torso joints, as defined in [5], plus a calculation of CoM were enough to discriminate the differences in motions of young and older people. Euclidean Distance was calculated between the spine base and head, using equation 2.…”
Section: Feature Encodingmentioning
confidence: 92%